Analysis of defect structures in silicon solar cell materials. - Mena, Manolo G.
Three (3) solar cells fabricated from EFG ribbons were subjected to quantitative defect analysis on several surface planes. The internal planes were observed by removing surface layers of silicon atoms by chemical dissolution. The results show that the average dislocation pit density varies from one surface plane to another. The procedures for chemical polishing and etching, as well as the process of quantitative defect analysis are also discussed.